Scaling resilience through use of co-designed radio programs in Baringo County, Kenya - Bullock, Renee M.; Majiwa, Hamilton; Saalu, Faith; Mundia, Julius; Mugi, Reginah; Ojulong, Henry; Mutai, Samuel; Akeno, Peter; Kukat, Lilian; Aturoit, Irene; Mossop, John; Kanyakera, Jacob (International Livestock Research Institute, 2024)
In the arid and semi-arid lands of Kenya, livestock keeping has been a cornerstone of livelihoods for centuries and, while it continues to be relevant, in recent decades landscape changes and climate related shocks and stresses are compounding increasing pressures in most livestock dependent households and communities. As the incidence of droughts and uncertain rain increases, finding pasture and water has become more difficult. Subsequently rates of food insecurity and precarity are rising. Pastoralists and agro-pastoralists are seeking knowledge on climate adaptation and are implementing innovative practices to better cope with changing realities that shape many aspects of their daily life. Diversification into food and crop production is one option that can support increased resilience to climate shocks. While maize is a commonly grown crop across Kenya, farmers in drylands often encounter challenges during production, primarily stemming from poor harvests caused by the crop’s vulnerability to harsh climatic conditions, leading to crop failure. On the other hand, drought tolerant crops (DTCs) perform well under low rainfall conditions and support livelihoods in many arid and semi-arid locations, as experience in lower eastern counties has shown. Widely considered to be “women’s” crops, DTCs such as sorghum and millet often rely disproportionately on women’s labor inputs. Women are typically responsible for most stages of their production including planting, weeding, harvesting and postharvest management, such as threshing, winnowing and storage. However, decision-making about production — including consumption and selling — may not always be in the hands of women. Men assume control over harvests and this decision-making power can increase with commercialization of these crops. Efforts to address these inequitable relations and behaviors include socio-technical bundling that combines technical information about climate smart